Relationship among Liveweight and Body Dimensions of the Greater Cane Rat (Thrynomys swinderianus) (2021)
The objective of this study was to predict the live weight (LW) of domestically kept Grasscutters from some morphological parameters. The study was carried out at the Grasscutter section of FAK Farms, Apata, Ibadan. Data were recorded on body length (BL), tail length (TL), heart girth (HG), wither height and head length (HL) and body weights of 45 animals (25 females and 20 males) selected at random. Body weights and linear body measurements were recorded for the animals at 3, 6, 9 and 12 months of age using the simple kitchen digital weighing balance and traditional tape measure respectively and the data obtained were subjected to descriptive statistics, Pearson correlation and regression analysis (P=0.05). Mean body length, tail and head lengths, heart girth and wither height were 51.38±3.03cm, 16.76±1.05cm, 10.01±0.42cm, 28.90±1.39cm and 13.66±0.75cm respectively for the male Grasscutters and 45.92±10.01cm, 14.62±0.84cm, 9.40±0.42cm, 28.06±1.41cm and 13.83±0.78cm respectively for the female Grasscutters. The correlation coefficients between LW and body measurements ranged from 0.251 to 0.909 for the male grasscutters and 0.347 to 0.945 for the female grasscutters with the highest correlation of 0.909 and 0.945 for the association between liveweight (LWT) and HG for males at 12 months of age and females at 9 months indicating sexual dimorphism. The coefficients of determination (R2) for the prediction equations recorded highest for heart girth {LWT= -0.101+0.095HG (82.6%)} at 12 months and {LWT= -2.671+0.148HG (89.4%)} at 9 months for the male and female Grasscutters respectively. Using the linear function from the R2 value, BL, WH and HG were better predictors of LW than TL and HL. The best predictor of body weight was heart girth for both the male and the female. In conclusion, the use of BL, WH and HG in a given function explained better the variation in LW than the use of just one body measurement and can provide a basis for selection.